Implementation of the rights of children under international law: The ideal and reality - Qanet, Ghulam Mohammad; Eishan Jan, Mohammad Naqib; Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali (LexisNexis M Sdn Bhd, 2021)
This article focuses on a set of issues pertaining to the rights of children as elaborated in the international legal instruments. Although the evolution of the rights of children can be traced in 18th and 19th Centuries, a more elaborate definition and view derived mainly from a number of United Nations (‘UN’) conventions dating from the late 1950’s until the present day.